2022
DOI: 10.1093/nar/gkac343
|View full text |Cite
|
Sign up to set email alerts
|

Control of bacterial immune signaling by a WYL domain transcription factor

Abstract: Bacteria use diverse immune systems to defend themselves from ubiquitous viruses termed bacteriophages (phages). Many anti-phage systems function by abortive infection to kill a phage-infected cell, raising the question of how they are regulated to avoid cell killing outside the context of infection. Here, we identify a transcription factor associated with the widespread CBASS bacterial immune system, that we term CapW. CapW forms a homodimer and binds a palindromic DNA sequence in the CBASS promoter region. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Next, we investigated how Ssc-CBASS is activated by Φ80ɑ-vir. We first considered the possibility of transcriptional activation of the operon during infection, as was reported for the type III CBASS of Escherichia coli upec-117 28 . RT-qPCR, however, failed to detect an increase in the transcription of the Ssc-CBASS genes upon infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated how Ssc-CBASS is activated by Φ80ɑ-vir. We first considered the possibility of transcriptional activation of the operon during infection, as was reported for the type III CBASS of Escherichia coli upec-117 28 . RT-qPCR, however, failed to detect an increase in the transcription of the Ssc-CBASS genes upon infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] We recently showed that E. coli upec-117 CBASS protects bacteria against infection by phage λ, and that the system's predicted MTA/SAH-family nucleosidase Cap17 is required for immunity, while Cap18 is dispensable for immunity. 10 These data show that Cap18 is not the primary effector of the E. coli upec-117 CBASS system, suggesting an accessory role for the protein. Our structure of Cap18 shows that this protein lacks a recognized second messenger binding domain, suggesting that its activity is unlikely to be modulated by second messengers produced by its cognate CD-NTase.…”
Section: Structure Of Escherichia Coli Upec-117 Cap18mentioning
confidence: 85%
“…CBASS effector proteins, including the CapV phospholipase and the NucC and Cap4 dsDNA endonucleases, are activated by the cyclic di‐ or trinucleotide second messenger produced by their cognate CD‐NTase 16–18 . We recently showed that E. coli upec‐117 CBASS protects bacteria against infection by phage λ, and that the system's predicted MTA/SAH‐family nucleosidase Cap17 is required for immunity, while Cap18 is dispensable for immunity 10 . These data show that Cap18 is not the primary effector of the E. coli upec‐117 CBASS system, suggesting an accessory role for the protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations